2018
DOI: 10.1109/tmm.2018.2829162
|View full text |Cite
|
Sign up to set email alerts
|

A Multiview Multimodal System for Monitoring Patient Sleep

Abstract: Clinical observations indicate that during critical care at the hospitals, a patient's sleep positioning and motion have a significant effect on recovery rate. Unfortunately, there is no formal medical protocol to record, quantify, and analyze motion of patients. There are very few clinical studies that use manual analysis of sleep poses and motion recordings to support medical benefits of patient positioning and motion monitoring. Manual processes do not scale, are prone to human errors, and put strain on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…When a subject performs activity in a dynamic environment, self and inter-object occlusion may occur. Multi-view human activity recognition helps to prevent a complete loss of information when occlusion appears in a single camera by providing information from other cameras [5,11]. Previous findings have indicated that employing multiple view increased the recognition rate of human activity in a dynamic environment [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When a subject performs activity in a dynamic environment, self and inter-object occlusion may occur. Multi-view human activity recognition helps to prevent a complete loss of information when occlusion appears in a single camera by providing information from other cameras [5,11]. Previous findings have indicated that employing multiple view increased the recognition rate of human activity in a dynamic environment [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Occlusion causes information loss and failure in single-view human activity recognition [1]. Previous researchers [2][3][4][5][6][7] have attempted to resolve this issue with the use of multiple cameras providing different angles of view [1,6] and enabling 3D posture representation [8,9]. Multi-view human action recognition (MVHAR) has a wide range of applications, including in systems for surveillance [4,10] and human behavior monitoring [5,11].…”
Section: Introductionmentioning
confidence: 99%
“…2, many researchers have attempted to develop contactless monitoring systems for various applications. Previous methods for monitoring people can be divided into 1) vision-based [4][5][6][7][8][9][10][11][12][13], 2) wearable-based [14][15][16][17][18][19][20][21], and 3) head-gaze-based technologies [22][23][24][25][26][27][28][29][30][31]. Vision-based methods usually detect and track the pose or movements of medically vulnerable people using user images captured by cameras.…”
Section: Figure 1: Examples Of Medically Vulnerable Peoplementioning
confidence: 99%
“…They used computer vision tasks such as: face detection and recognition, facial action unit detection and expression recognition, head pose detection and recognition, sound and light level detection, and other activity detection. A research multi-view multi-modal systems for sleep monitoring of patients [37]. Sleeping position is very vital for the recovery of a patient for some diseases in ICU, so their model has concentrated this kind of detection in ICU.…”
Section: Review Of Some Recent State-of-the-artsmentioning
confidence: 99%